Mechanism for Issuing Waqf Land Certificates Based on Village Letter C Rights - Febramadhani, Intan; Sri Darmadi, Nanang (TABELLIUS: Journal of Law, 2025)
The issuance of waqf land certificates is an important part of land administration to provide legal certainty for land declared as waqf. This study aims to analyze the mechanism for issuing waqf land certificates based on village Letter C rights at the Tegal Regency Land Office, covering administrative stages, land technicalities, obstacles encountered, and solutions implemented in the registration process. The author employed an empirical legal research method, based on field studies and examining applicable legal provisions in relation to the realities of society. The data analysis technique employed descriptive qualitative analysis, which involved analyzing problems by obtaining data directly from respondents. This study concludes that the issuance of waqf land certificates with Letter C village rights in Tegal Regency can be implemented effectively if there is synergy between the village, the nazhir, and the Land Office, supported by complete documents and certainty of physical data. These findings are expected to serve as recommendations for strengthening waqf land registration governance to ensure orderly land administration and provide legal protection for waqf assets.